Ethics between the Lines: Narratology and Literary Non-Fiction (KULT_online, 2014)
Towards A Critical Ethical Narratology is a post-structuralist and interdisciplinary work which makes use of advances in narratology and other areas of literary theory whilst observing the turn towards ethical criticism in literature. This approach is applied to the developing genre of literary non-fiction and the ethics implicit in narrating real-life events in recent memory as literature.